Is Erectile Dysfunction an Early Indicator of Cardiovascular Disease - Tunç, Lütfi; Küpeli, Bora; Tuncel, Altuğ; Biri, Hasan; Kordan, Yakup; Deniz, Nuri; Bozkırlı, İbrahim (Fırat University, 2007)
Objectives: Our aim was to evaluate cardiovascular health who applied to our clinic for erectile dysfunction. These patients neither had any history of cardiovascular disease nor used medical or surgical treatment for atherosclerotic coronary artery disease. Material and Methods: 100 male patients had been included for this study that were applied to our clinic for erectile dysfunction and planned to be started sildenafil sitrate. As a diagnosis criteria we used the first 5 questions of International Index for Erectile Function and the patients whose score was below 21, were included to our study. We performed blood chemistry, profile of hormones and penile doppler ultrasonography to all patients. The patients had been performed holter monitorisation. Electrocardiography, ecocardiography, myocard perfusion sintigraphy with talium and coronary angiography were performed to the patients according to neccessity who had ST segment depression seems to be ischemia. Results: Mean ages of patients were 50.0±13.0 (22-76). Further investigations were performed to 40 patients who had ST depression seems to be ischemia according to the results of Holter Monitorisation. According to the results of these investigations 3 patients were (3%) transferred for coronary bypass operation. 25 patients (25%) have been diagnosed as atherosclerotic coronary artery disease and medical treatment was started to these patients. Conculation: ED patients with no history of symptomatic cardiovascular disease may have atherosclerotic coronary artery disease with significiant rates. Therefore, ED may be an early predictor for cardiovascular disease in many patients and we believe that these patients should be investigated carefully about cardiovascular diseases. ©2007, Firat University, Medical Faculty

Giriş: Erektil disfonksiyon (ED) nedeni ile başvuran ve öyküsünde herhangi bir kardiyovasküler hastalığı olmadığı ve/veya ASKH nedeniyle medikal ya da cerrahi tedavi almamış hastalarda kardiyovasküler patoloji yönünde araştırma yapmanın gerekliliğini araştırdık. Gereç ve Yöntem: Kliniğimize ED şikayeti ile başvuran ve medikal tedavi olarak sildenafil sitrat başlanması planlanan 100 erkek hasta çalışmada yer aldı. ED tanı kriteri olarak tüm hastaların Uluslararası Erektil Fonksiyon İndeksi'nin ilk beş sorusu (IIEF-5)'na göre skoru
Erektil Disfonksiyon Kardiyovasküler Hastalığın Erken Habercisi Olabilir mi?